Facile synthesis of calcium borate nanoparticles and the annealing effect on their structure and size - Haghiri, Maryam Erfani; Saion, Elias; Soltani, Nayereh; Hashim, Mansor; Wan Abdullah, Wan Saffiey; Navasery, Manizheh (MDPI AG, 2012)
Calcium borate nanoparticles have been synthesized by a thermal treatment method via facile co-precipitation. Differences of annealing temperature and annealing time and their effects on crystal structure, particle size, size distribution and thermal stability of nanoparticles were investigated. The formation of calcium borate compound was characterized by X-ray diffraction (XRD) and Fourier Transform Infrared spectroscopy (FTIR), Transmission electron microscopy (TEM), and Thermogravimetry (TGA). The XRD patterns revealed that the co-precipitated samples annealed at 700 °C for 3 h annealing time formed an amorphous structure and the transformation into a crystalline structure only occurred after 5 h annealing time. It was found that the samples annealed at 900 °C are mostly metaborate (CaB2O4) nanoparticles and tetraborate (CaB4O7) nanoparticles only observed at 970 °C, which was confirmed by FTIR. The TEM images indicated that with increasing the annealing time and temperature, the average particle size increases. TGA analysis confirmed the thermal stability of the annealed samples at higher temperatures.